Response Evaluation of Patients Undergoing Transarterial Chemoembolization (TACE) for Hepatocellular Carcinoma with Respect to Tumour Size, Number of Lesion, and Alpha-Fetoprotein (AFP) Level - Adaninggar PN; Ulfa Kholili; Ummi Maimunah; Poernomo B Setiawan; Iswan A Nusi; Herry Purbayu; Titong Sugihartono; Budi Widodo; Husin Thamrin; Amie Vidyani (The Indonesian Society for Digestive Endoscopy, 2016)
Background: Transarterial chemoembolization (TACE) is widely used as a palliative treatment for unresectable hepatocellular carcinoma (HCC). TACE is also used as bridging therapy before liver transplantation to avoid tumour progression and considered for downstaging to fulfill tumour resection or liver transplantation criterias. This study aimed to evaluate response of TACE in unresectable HCC according to changing of tumour size, number of lesion, and AFP level.Method: Retrospectively, we evaluate 69 HCC patients who underwent TACE in Dr. Soetomo General Hospital in January 2012-June 2015, including their age, sex, aetiologies, and Barcelona Clinic Liver Cancer/BCLC staging. Laboratory examinations such as complete blood count (hemoglobin/Hb, leucocyte, thrombocyte), liver function test (aspartate aminotransferase/AST, alanine aminotransferase/ALT, bilirubin, albumin, international normalized ratio/INR), alpha-fetoprotein/AFP level, and abdominal CT-scan were performed before and 1 month post-TACE. Data was analysed using paired t-test.Results: 69 patients with mean age of 51.81 ± 12.8 years old, predominantly 76.8% males, the most common aetiology was hepatitis B 68.1%, 92.8% BCLC B, 64.3% with stable disease, none achieved complete response, 97.1% had tumour size 5 cm, 69.6% had single tumour, and 55.7% had AFP level 1000 ng/mL. There was a significant increase in tumour size and number of lesions in 1 month post-TACE that were approximately 1.76 cm and 2.33, respectively, and there was no significant difference between AFP level before and 1 month post TACE.Conclusion: In 1 month post TACE evaluation, there was a significant increase of tumour size and number of lesion, but there was no significant alteration in AFP level. TACE might be performed repeatedly with shorter evaluation interval than 1 month to achieve better response.